Kombinasi Jamur Tiram Putih (Pleurotus Ostreatus) Dengan Ikan Patin Dalam Pembuatan Bakso Ikan - Nuraisah '; Raswen Efendi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The study aimed to obtain the proper formulation in the manufacture of white oyster mushroom meatballs. The research was carried out experimentally using completely randomized design (CRD) with five treatments, namely : JP1 (95% White Oyster Mushroom : 5% Catfish), JP2 (90% White Oyster Mushrooms : 10% Catfish), JP3 (85% White Oyster Mushroom : 15% catfish), JP4 (80% White Oyster mushrooms : 20% catfish), JP5 (75% White Oyster mushrooms : 25% catfish). The results showed that the combination of oyster mushroom with catfish significantly effect on the moisture content, ash content, fat content, flavor and texture, on organoleptic but did not significantly affect the color, flavor and overall acceptance. The best combination was JP4 (80% White Oyster Mushroom : Catfish 20%) which content 75,61% water, 2,01% ash, 0.65% fat, grayish white color, the aroma of fish,distinctive flavor fish balls, chewy texture and overall assessment by panelists preferred meatballs Keywords:Meatballs, WhiteOyster Mushrooms and Catfish